2013
DOI: 10.4236/aim.2013.35060
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Detection of Viruses in Water and Wastewater

Abstract: Viruses present in water might be harmful for human health and life. Nowadays over 100 pathogenic human virus species occur in water polluted with sewage. Chlorination, which is the most popular disinfection method is not able to remove easily viruses from treated water. Due to this, it's necessary to detect viruses in water before treatment in order to determine disinfectant dose and to ensure the sanitary safety level of treated water. The aim of this article is to review viruses detection methods as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The accuracy of detection of viruses depends on the sample volume, nucleic acid extraction yield (for nucleic acid-based methods) and purity ( Bofill-Mas and Rusiñol, 2020 ; Haramoto et al, 2018 ; Hryniszyn et al, 2013 ; Sidhu et al, 2013 ). A study conducted by Hjelmsø et al (2017) showed that both the concentration of nucleic acids and the nature of the methods used for the extraction significantly influence the results of viral metagenomic analyses, particularly those of viral community composition, viral specificity, and viral pathogen detection.…”
Section: Methods Of Pre-treatment Of Wastewater Samplesmentioning
confidence: 99%
“…The accuracy of detection of viruses depends on the sample volume, nucleic acid extraction yield (for nucleic acid-based methods) and purity ( Bofill-Mas and Rusiñol, 2020 ; Haramoto et al, 2018 ; Hryniszyn et al, 2013 ; Sidhu et al, 2013 ). A study conducted by Hjelmsø et al (2017) showed that both the concentration of nucleic acids and the nature of the methods used for the extraction significantly influence the results of viral metagenomic analyses, particularly those of viral community composition, viral specificity, and viral pathogen detection.…”
Section: Methods Of Pre-treatment Of Wastewater Samplesmentioning
confidence: 99%
“…In vitro growth methods such as cell culture are the most pronounced traditional standards used to identify and detect the occurrence of HEV in environmental samples [ 82 , 98 , 99 ]. Cell culture is a technique whereby a microorganism’s cells are grown at a carefully controlled condition outside of the living animal [ 100 ].…”
Section: Conventional Methods For the Identification Of Hev In Envmentioning
confidence: 99%
“…Here, the virus-like particles are counted using fluorescent nucleic acid stains through visualisation [ 107 , 108 , 109 , 110 ]. Flow cytometry and vortex flow filtration (VFF) have also been used for the quantification and counting of virus-like particles and prokaryotes in aquatic environments [ 98 , 111 , 112 ]. Figure 3 exhibits the numerous molecular approaches that have been used in the diagnostics and identification of HEV in environmental samples.…”
Section: Conventional Methods For the Identification Of Hev In Envmentioning
confidence: 99%
“…Various methods like isothermal amplification of target genes [51] , biosensors [125] , microarrays [126] , [127] , culture-based assays [128] , metagenomics [129] and polymerase chain reaction (PCR) and its types [130] , [131] are employed for the detection and quantification of the virus in the environmental samples ( Table 2 ). E. coli and f2 phage [51] , Poliovirus-1 (PV-1) Virome [47] , [52] , [53] , [54] , and HAV [55] were used as indicators for the evaluation of persistence and occurrence of CoV in environment wastewaters ( Table 1 , Table 2 ).…”
Section: Detection Of Virus In Environmental Matricesmentioning
confidence: 99%